1992
DOI: 10.1111/j.1471-4159.1992.tb08440.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the 5‐Hydroxytryptamine Receptor Modulating the Release of 5‐[3H]Hydroxytryptamine in Slices of the Human Neocortex

Abstract: In the rat brain, the presynaptic 5-hydroxytryptamine (5-HT) autoreceptors located on 5-HT terminals correspond to the 5-HT1B subtype. The presence of a 5-HT receptor probably located on 5-HT nerve endings and modulating transmitter release in the human neocortex has been reported, but its detailed pharmacological characterization is not yet available. On the other hand, receptor binding and autoradiographic results indicate that the 5-HT1B receptor subtype is not present in the human brain. We, therefore, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 41 publications
2
30
0
Order By: Relevance
“…Using an in vivo elec trophysiologic paradigm, it was recently shown that these u2-adrenergic heteroreceptors in the rat hip pocampus are tonically activated by endogenous NE (Mongeau et al 1993), as is the case in the human brain (Galzin et al 1992;Feuerstein et al 1993). Small doses (2 �g/kg and 10 �g/kg IV) of the u2-adrenergic agonist clonidine enhance 5-HT neurotransmission, an effect that is abolished by a 6-hydroxydopamine (6-0HDA) pretreatment and blocked by the u2-adrenergic an tagonist yohimbine (0.1 mg/kg IV).…”
mentioning
confidence: 99%
“…Using an in vivo elec trophysiologic paradigm, it was recently shown that these u2-adrenergic heteroreceptors in the rat hip pocampus are tonically activated by endogenous NE (Mongeau et al 1993), as is the case in the human brain (Galzin et al 1992;Feuerstein et al 1993). Small doses (2 �g/kg and 10 �g/kg IV) of the u2-adrenergic agonist clonidine enhance 5-HT neurotransmission, an effect that is abolished by a 6-hydroxydopamine (6-0HDA) pretreatment and blocked by the u2-adrenergic an tagonist yohimbine (0.1 mg/kg IV).…”
mentioning
confidence: 99%
“…When stimulated via electrical means or by depolarization with agents such as potassium ions, 5-HT can be released from nerves, in vitro (Monroe and Smith, 1985;Galzin et al, 1992;Moret and Briley, 1997). In the eye, serotonin-containing nerve ®bers have been localized in the iris-ciliary bodies and corneas of guinea pigs, rats and rabbits (Uusitalo et al, 1982;Tobin et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
“…The results of several recent studies suggest that in very early stages of development 5-HT 1B/1D and 5-HT 1A receptors may act as 5-HT autoreceptors, so that 5-HT synthesis, storage, and uptake may be down-regulated by 5-HT itself (Héry et al, 1999;Mouillet-Richardet al, 2000;Roberts et al, 2001;Rumajogee et al, 2004). It has been suggested that 5-HT 1B autoreceptors diminish 5-HT release from axon terminals and varicosities (Galzin et al, 1992), while 5-HT 1A autoreceptors inhibit firing of serotonergic neurons (Sprouse and Aghanian, 1987;Héry et al, 1999;. Furthermore, it has recently been observed that the lack of 5-HT 1B or 5-HT 1A receptors is associated with a significant increase in the number of serotonergic neurons in primary cultures from embryonic raphe (Rumajogee et al, 2004).…”
Section: Discussionmentioning
confidence: 99%